Tropheryma whipplei endocarditis presenting as chronic valvular disease: A case report and review of literature - Julia R. Naso; Davie Wong; Daniel R. Wong; Chien-Hung Chen; Linda M.N. Hoang (Elsevier, 2019)
Whipple's endocarditis is a rare but treatable infectious disease. We discuss the diagnostic work-up of a case lacking classic endocarditis features. Current challenges in diagnosis and treatment of this under-recognized infection are highlighted. This case underscores the necessity of considering Whipple's endocarditis in the differential diagnosis for chronic valvular disease. Keywords: Whipple's endocarditis, Whipple's disease, Tropheryma whipplei, Endocarditis, Culture-negative endocarditis